Spectrophotometric flow injection system for determination of Zn2+ in ophthalmic formulations using Alizarin red S - Fatibello-Filho, Orlando; Vieira, Heberth Juliano (Eclética Química, 2009)
A spectrophotometric flow injection method for the determination of Zn(II) in ophthalmic formulations was developed. In this work, Zn(II) ion was complexed with Alizarin red S in borate buffer solution (pH 9.0) and the chromophore produced was monitored at 520 nm. The analytical curve was linear in the Zn(II) concentration range from 6.05 x 10-6 to 1.50 x 10-4 mol L-1 with a detection limit of 3.60 x 10-6 mol L-1. Recoveries ranged from 96.3 to 105 % and a relative standard deviation of 1.2 % (n = 10) for 5.5x10-5 mol L-1 Zn(II) reference solution were obtained. The sampling rate was 60 h-1 and the results obtained of Zn(II) in ophthalmic products using this procedure are in close agreement with those obtained using a comparative spectrophotometric procedure at 95 % confidence level.